PENGUATAN RESOLUSI KONFLIK BERBASIS TRADISI SUNNAH NABI - Alamsyah, Alamsyah (Asy-Syari'ah, 2020)
Abstract: This paper examines the theological foundation of conflict resolution from the treasury of the Prophet's Sunnah. This foundation is important to be studied as an epistemology and argument for strengthening conflict resolution in the reconstruction of Islamic science in the modern era. The Sunnah of the Prophet as one of the important sources of Islamic teachings after the Qur'an will strengthen the theological foundation of conflict resolution. This study uses the document study method, with data sources from hadith texts and classical literature to then be processed and analyzed qualitatively using a historical approach. Research findings show that the Sunnah of the Prophet has exemplified the basis and model of conflict resolution or conflict resolution, such as conflict resolution in laying the Hajar Aswad stone, the Medina charter and the Hudaibiyah agreement. The Sunnah of the Prophet as written in the hadith texts is an important source in extracting and determining conflict resolution in society. The Sunnah of the Prophet brings living values in society and is followed by its members. Because Islam is a religion that is embraced by the majority of Indonesian people, the conflict resolution based on the Sunnah of the Prophet provides a better direction. The Sunnah of the Prophet teaches that the model of conflict resolution depends on the type of conflict and the situation and condition of the people who are experiencing conflict. Conflict resolution in the traditions of the Sunnah of the Prophet has developed into the reality of society called local wisdom. Therefore, local wisdom is actually a development of the teachings of the Sunnah of the Prophet who has experienced actualization. The important thing to do is to contextualize and reactivate the values of wisdom in the Sunnah of the Prophet into a model of conflict resolution to remain relevant in the midst of current developments. The various values of conflict resolution or reconciliation in the Sunnah of the Prophet are relevant as approaches to conflict resolution in order to create a harmonious family and a united and peaceful Indonesian state.Â Abstrak: Tulisan ini mengkaji tentang landasan teologis resolusi konflik dari khazanah Sunnah Nabi. Landasan ini penting dikaji sebagai epistemologi dan argumentasi penguatan resolusi konflik dalam rekonstruksi ilmu keislaman di era moderen. Sunnah Nabi sebagai salah satu sumber penting ajaran Islam setelah al-Qurâ€™an akan memperkuat landasan teologis resolusi konflik. Penelitian ini menggunakan metode studi dokumen, dengan sumber data dari teks-teks hadis dan literatur klasik untuk kemudian diolah dan dianalisis secara kualitatif dengan menggunakan pendekatan historis. Temuan penelitian menunjukkan bahwa dalam Sunnah Nabi telah banyak dicontohkan dasar dan model penyelesaian konflik atau resolusi konflik, seperti penyelesaian konflik dalam peletakkan batu Hajar Aswad, piagam Madinah dan perjanjian Hudaibiyah. Sunnah Nabi sebagaiÂmana tertulis dalam teks-teks hadis adalah satu sumber penting dalam penggalian dan penentuan resolusi konflik dalam masyarakat. Sunnah Nabi membawa nilai-nilai yang hidup dalam masyarakat dan diikuti oleh anggotanya. Oleh karena Islam merupakan agama yang dipeluk oleh mayoritas masyarakat Indonesia, maka resolusi konflik berbasis Sunnah Nabi memberikan arah lebih baik. Sunnah Nabi mengajarkan bahwa model penyelesaian konflik tergantung kepada jenis konflik serta situasi dan kondisi masyarakat yang mengalami konflik. Resolusi konflik dalam tradisi Sunnah Nabi telah berkembang ke dalam realitas masyarakat yang disebut dengan kearifan lokal. Oleh karena itu maka kearifan lokal sebenarnya merupakan pengembangan dari ajaran Sunnah Nabi yang telah mengalami aktualisasi. Hal yang penting dilakukan adalah melakukan kontekstualisasi dan reaktualisasi nilai-nilai kearifan dalam Sunnah Nabi ke dalam model reolusi konflik agar tetap relevan di tengah perkembangan kekinian. Berbagai nilai-nilai resolusi konflik atau islah dalam Sunnah Nabi tersebut relevan sebagai pendekatan dalam penyelesaian konflik agar terwujud keluarga yang harmoni dan negara Indonesia yang bersatu dan damai.